An exploratory examination into the relationship between students’ perceptions of career decision-making self-efficacy and family members’ work experiences. - Hutchison, Sarah (My University, 2007)
The present research study examines the possible relationship between students’ career decision-making self-efficacy (CDMSE) and their perceptions of their family members’ job satisfaction and job insecurity. The present research uses a quantitative, non-experimental, cross-sectional research design, on a sample of 148 subjects drawn from a sample of first year Psychology students from the University of the Witwatersrand, South Africa. The Career Decision Self-Efficacy scale was used to measure career decision-making self-efficacy (Betz & Taylor, 2001), Warr, Cook and Wall’s (1979) Overall Job Satisfaction scale to measure job satisfaction (Short, 1996) and the Job Insecurity scale developed by Ashford, Lee and Bobko (1989) to measure job insecurity. The statistical procedures used to analyse the data, included correlations to test the first hypothesis, which proposed a relationship between students’ CDSME and their perceptions of their family members’ job satisfaction and the second hypothesis, assumed a relationship between students’ CDMSE and their family members’ job insecurity. A Stepwise Multiple Regression was performed to examine the above hypotheses. The results reported a significant relationship between students’ CDMSE and their perceptions of their family members’ job satisfaction. However, there was insufficient evidence to support the relationship between students’ CDMSE and their perceptions of their family members’ job insecurity.
MA research report - Student Number : 0105436V - School of Human and Community Development - Faculty of Arts
Keywords: student's perceptions of career decision-making; self-efficacy; family member's work experience